The mylohyoid line is highly variable but does not affect the microarchitecture of the edentulous alveolar bone - an anatomical micro-CT study - Danijel Domic; Julia Kappenberger; Kristina Bertl; Lena Hirtler; Patrick Heimel; Christian Ulm (BMC, 2024)
Abstract Objectives To evaluate in the absence of teeth the variability of the mylohyoid line (ML), the microarchitecture of the adjacent bone, and whether the variable prominence/width of the ML is associated with the quality of the adjacent bone. Methods µCT scans of 28 human mandibles from anatomical specimens were analyzed. The following parameters were assessed in four edentulous areas (first and second premolar (PM), first, second, and third molar (M1/2/3)): ML width, cortical thickness (CtTh), average cortical- (Avg.Ct.BV/TV), and trabecular bone volume fraction (Avg.Tb.BV/TV). Results The ML width increased from the PM towards the M2 region, which also showed the highest variance (range: 0.4-10.2 mm). The CtTh showed a decrease in the M3 region, while Avg.Ct.BV/TV and Avg.Tb.BV/TV hardly differed among the regions. In the multivariable model on the effect of the various parameters on the ML width, only gender and tooth region were significant. Specifically, male specimens were associated with a wider ML width compared to female specimens and the M2 region was associated with a wider ML width compared to the other tooth regions. Conclusion The ML width was not associated with the cortical and trabecular bone quality in the adjacent bone, while gender and tooth region had a significant effect. Specifically, the ML width was lower in female, but peaked in the M2 region with a median width of 3-4 mm. Clinical relevance From a clinical point of view, it was confirmed that the ML is in general a highly variable structure, especially in the M2 region, but the ML width does not allow any conclusions on the bone quality. Altogether, this underlines the need for an individual and accurate diagnostic prior to any surgical intervention.